Product Quality and Brand Experience on Repeat Purchase Interest in Implora Lipsticks - Nurlela Nurlela; Muhamad Stiadi; Andry Stepahnie Titing (Universitas 17 Agustus 1945 Semarang, 2023)
The research was centred on a demographic comprising individuals who were consumers of Implora lipstick within the local community. This research employed quantitative research methods to examine two primary objectives: (1) to evaluate the impact of product quality on the intention to repurchase implora lipsticks in Kolaka Regency, and (2) to analyse the influence of brand experience on the intention to repurchase implora lipsticks in Kolaka Regency. To evaluate the dependability and accuracy of the research instrument, a battery of tests was administered by the researchers utilising the statistical software SPSS 25.0. The evaluation of the measurement model, also known as the outer model, and the structural model, referred to as the inner model, is performed through the utilisation of Structural Equation Modelling (SEM) with the application of Partial Least Squares (PLS) methodology. The findings of the research demonstrate a significant and favourable association between the attributes of product quality and the degree of inclination towards engaging in subsequent purchases. The assertion is substantiated by empirical evidence, as indicated by a t-statistic of 5.648 and a corresponding P-value of 0.000. Moreover, recent studies have unveiled that characteristics linked to the brand encounter demonstrate a positive and statistically significant impact on the level of propensity to engage in repeat purchasing behaviour. The assertion provided is supported by a t-statistic value of 3.543, which is accompanied by a P-Value of 0.000.